2020
DOI: 10.1002/stc.2529
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of inerter‐based dampers for vortex‐induced vibration control of long‐span bridges: A comparative study

Abstract: Summary Inerter‐based dampers (IBDs) have been proposed to enhance the efficiency of conventional tuned mass dampers (TMDs) in controlling wind‐induced vibration of civil structures recently. In this paper, four different IBDs, with each featuring a specific combination of dashpot–spring elements in series or in parallel with the inerter device, are applied to control the vortex‐induced vibration (VIV) of long‐span bridges. The governing equations of the bridge–IBD system under the effect of VIV are establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It was found that the performance of the C1 arrangement in suppressing vortex-induced vibration was inferior to the traditional arrangement in [21], consistent with the conclusion in [23]. In 2020, Xu et al [25] compared the performance of C2-C4 arrangements in suppressing vortex-induced vibration.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It was found that the performance of the C1 arrangement in suppressing vortex-induced vibration was inferior to the traditional arrangement in [21], consistent with the conclusion in [23]. In 2020, Xu et al [25] compared the performance of C2-C4 arrangements in suppressing vortex-induced vibration.…”
Section: Introductionmentioning
confidence: 62%
“…where Y(jω) is the admittance function of any IDVA and j � �� � − 1 √ . Substitute ( 6) into (25), and multiply both sides of the equation by ϕ i (x), and then integrate x from 0 to L. After a dimensionless calculation process, one can obtain…”
Section: E Optimal Installation Position Of the Idvamentioning
confidence: 99%
“…Meanwhile, compared to the large one-terminal mass in the isolation system, the inerter system does not need much installation space or actual physical mass [31]. To date, utilizing the superiorities of enhancement mechanisms and two-terminal fexible installation, the inerter system has been applied in various aboveground civil engineering structure forms, such as buildings [32], bridges [33], wind turbine towers [34], storage tanks [35], and suspension cables [36]. Multiple experiments [24,25] and engineering projects [25,37] demonstrated its good vibration mitigation efect and comprehensive applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al 34 investigated the effect of inerter span length of TMDI, indicating that the control efficiency increases as inerter spans longer girder length. Furthermore, Xu et al 35 compared different layouts of inerter‐based dynamic vibration absorbers for bridge VIV control. Dai et al 36 utilized a maxwell element to replace the liner dashpot in TMDI and examined its performance in bridge VIV control.…”
Section: Introductionmentioning
confidence: 99%